New bromopyrrole alkaloids from the marine sponge Agelas sp. Issue 19 (11th May 2017) - Sun, Ya-Ting; Lin, Bin; Li, Sheng-Ge; Liu, Man; Zhou, Yong-Jun; Xu, Ying; Hua, Hui-Ming; Lin, Hou-Wen
Abstract: Chemical investigation of the marine sponge Agelas sp. collected from the South China Sea resulted in the isolation of four new dimeric bromopyrrole alkaloids, including hexazosceptrin (1 ) with a rare cyclohexane-fused-cyclobutane skeleton, agelestes A and B (2–3 ), the sceptrin analogues without any aminoimidazole substitution, and (9 S, 10 R, 9′ S, 10′ R )-nakamuric acid (4 ), of which the absolute configuration was confirmed for the first time. The structure elucidation and absolute configuration assignments were unambiguously determined via extensive spectroscopic analyses and the comparison of experimental and calculated electronic circular dichroic spectra. Compounds1 and4 exhibited moderate antimicrobial activity. Graphical abstract: